The Role of Phenolic Compounds as Anti-Inflammatory in Obese Individuals - Randenia, Nabila; Noer, Etika Ratna; Anjani, Gemala (GLOBAL HEALTH SCIENCE GROUP, 2024)
Dietary polyphenols have chemopreventive and protective roles in maintaining human health and disease. Strong antioxidant effects are exhibited by dietary polyphenols and flavonoids against reactive oxygen species (ROS) and cellular oxidative stress (OS), thereby protecting against OS-related pathological conditions or diseases. This study generally aims to see the impact of phenol and bioactive compounds on inflammation in obese individuals. The method used in this study is a literature review. The stages involved in this process encompass identifying the central topic or issue to be discussed, conducting a comprehensive search for pertinent references or literature related to the topic, thoroughly reading, evaluating, and analyzing the literature in alignment with the study objectives, and finally, composing a narrative report that presents the review findings along with a concise summary. The time frame for the analysis was April 2013 to June 2023. A total of 323 publications with phenolic compounds as anti-inflammatory in obese were identified. From the initial 323 studies, 12 studies were selected for final analysis. The search for relevant articles or references will be conducted in the online databases Science Direct, Springer, Wiley Library, PubMed, and Google Scholar. The keywords used to search for references are obesity, inflammation, phenol compounds, bioactive compounds, antioxidants, and antioxidants. This literature review found that out of the 12 articles reviewed, 12 had similarities, stating that interventions with different doses of phenol compounds can reduce inflammatory cytokines in obesity with different periods. Overall, antioxidant bioactive compounds regulate pro-inflammatory and anti-inflammatory cytokines, reduce oxidative stress by decreasing the accumulation of reactive oxygen species, and enhance antioxidant capacity and gene expression to prevent DNA damage in obese individuals.